If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2x-(-3+5x)=(-2x-2)
We move all terms to the left:
2x-(-3+5x)-((-2x-2))=0
We add all the numbers together, and all the variables
2x-(5x-3)-((-2x-2))=0
We get rid of parentheses
2x-5x-((-2x-2))+3=0
We calculate terms in parentheses: -((-2x-2)), so:We add all the numbers together, and all the variables
(-2x-2)
We get rid of parentheses
-2x-2
Back to the equation:
-(-2x-2)
-3x-(-2x-2)+3=0
We get rid of parentheses
-3x+2x+2+3=0
We add all the numbers together, and all the variables
-1x+5=0
We move all terms containing x to the left, all other terms to the right
-x=-5
x=-5/-1
x=+5
| 33x+198=891 | | 5(x+12)-20=40 | | 60x-300=900 | | )4(x+3)=x-14 | | 2x-15+3×=90 | | 9•x-15= | | 9•x-15=48 | | 2x²+4x−100=0 | | -4,8x+4=-3x-5 | | -x+3=2x-15 | | 2.x-7=101-x | | 6x–18=–x+3 | | 8x+2;x=1/4 | | 1000/10x=23 | | 9x-11=79. | | 3/x-1=4/2x+3 | | (3x+4)(3x−2)+(4−3x)(4+3x)=(2x−1)(2x+1)−(4x−4)(x+2) | | 17+(-x)+(-9)=4 | | (2x-4)²=5x-6 | | 98=7e | | .98=7e | | 9(4+n)=81 | | (5x-40)(8x-80)=0 | | (2x+10)+(3x+30)=180 | | 2x+10)+(3x+30)=180 | | 2x+1/4=7x-12/15 | | 50x=0.5 | | 3x+7x–6–2x=18 | | 2x-4-3x-9=6 | | 40x+35=5000 | | 15-(12x+3)+(27x–3)=75–18x | | 2(2x-5)-3(x+2)=5(2-x) |